Human Centric Approach in Smart Remanufacturing for End-Life-Vehicle (ELV)’s Stabilizer Bar - Khairul Nizam Suhaimin; Wan Mahmood, Wan Hasrulnizzam; Al Amin Mohamed Sultan; Zuhriah Ebrahim; Halimaton Hakimi; Syafiq Aziz (Malaysian Journal on Composites Science and Manufacturing, 2023)
This paper aims to develop a new recommended human-centric framework for the smart remanufacturing of End-Life-Vehicle (ELV)s stabilizer bars to enhance worker experiences. The human-centered method has been applied in various applications since its introduction. Still, there has been little consideration of worker experience challenges in developing the smart remanufacturing of ELV’s stabilizer bar concept. Data were analyzed using a regression model to evaluate the six hypotheses to generate the human-centric model. According to the research, five aspects of the human-centric model strongly correlate with worker experience: emotional, cognitive, intellectual, confidence and trust. However, only one aspect, behaviour, did not significantly correlate with worker experience. As a result, the conceptual framework excludes the minor aspect of worker experience in human-centric design. Recognizing the importance of smart remanufacturing of ELV’s stabilizer bar, this model is expected to be used as guidance to build a smart remanufacturing of ELV’s stabilizer bar system that specifically responds to human needs.